Pilot Study: Feasibility and Preliminary Outcome of the Psychotherapy Intervention with Parents of Leukaemia Children in Malaysia - Muhammad Syamsul Mat Zin; Azlinda Azman; Zarina Abdul Latiff; Loh C-Khai (Asian Social Work Journal, 2022)
Reporting the preliminary findings and the feasibility of a pilot group psychotherapy intervention study of one hour session for four sessions, also known as 'PERKASA Intervention' towards parents of children with leukaemia, conducted at one of the University Teaching Hospital (UTH) in Malaysia. In this Randomized Controlled Trial (RCT) design, a total of 19 parents agreed to participate and 11 participants were placed in the Treatment Group (TG), meanwhile eight parents were placed in the Control Group (CG). This study looked at the effects comparison between pre- and post-interventions, as well as reviewed the feasibility of the implementation of PERKASA Interventions. Feasibility refers to the evaluation of TG participants' feedback. PERKASA Intervention showed to positively impact stress, depression, anxiety, and coping strategies among TG at the pre and post stages. PERKASA Intervention has also been shown that it can be consistently used for targeted groups. The main challenge seen was the recruitment of participants during Covid-19 pandemic occurring all over the world. The data from this pilot study can be used as a reference for larger-scale studies in the future. This intervention was fully conducted by professionals from Medical Social Worker as therapists and the first to be implemented in Malaysia.